Aesthetic Surgery in Plastic Surgery Academia. (14th August 2020) - Perdikis, Galen; Eaves, Felmont F; Glassman, Gabriella E; Walker, Sallie; Huang, Li-Ching; Mast, Bruce; Damitz, Lynn; Rubin, J Peter; Serletti, Joseph M; Hansen, Juliana; Potochny, John; Kenkel, Jeffery; et al.
Abstract: Background: Aesthetic surgery is a critical component of academic plastic surgery. As institutions are placing increased focus on aesthetic surgery, there is an opportunity to identify factors that facilitate the creation and maintenance of successful aesthetic plastic surgery programs. Objectives: The aim of this study was to conduct a national survey to evaluate the current state of academic aesthetic surgery and to identify factors that contribute to success. Methods: A REDCap 122-question survey was developed and validated by members of the Academic Aesthetic Surgery Roundtable (AASR). The national survey was distributed to department chairs and division chiefs with active ACGME-approved plastic surgery programs (n = 92). Responses underwent Pearson's chi-squared, Wilcoxon rank-sum, and postselection inference analyses. AASR members convened to interpret data and identify best practices. Results: Responses were received from 64 of 92 queries (69.6%). The multivariate analysis concluded traits associated with successful academic aesthetic surgery practices included the presence of aesthetic surgery–focused, full-time faculty whose overall practice includes >50% aesthetic surgery ( P = 0.040) and nonphysician aesthetic practitioners who provide injection services ( P = 0.025). In the univariate analysis, factors associated with strong aesthetic surgery training programs included resident participation in faculty aesthetic clinics ( P = 0.034), aesthetic research ( P = 0.006), and discounted resident aesthetic clinics ( P < 0.001). Conclusions: The growth of academic aesthetic surgery practices represents a significant opportunity for advancement of resident training, departmental financial success, and diversification of faculty practices. By identifying and sharing best practices and strategies, academic aesthetic surgery practices can be further enhanced.